Composite heat stabilizer and preparation method thereof

By adding organozinc metal compounds, polyols and modified hydrotalcite to the rare earth thermal stabilizer, the problem of poor thermal stability in the initial stage and the zinc-based thermal stabilizer is easily 'zinc burned', achieving high efficiency, environmental protection and long-term stability effects of the composite thermal stabilizer.

CN119529390AActive Publication Date: 2025-02-28台州联成新材料有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411859938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing rare earth thermal stabilizers have poor thermal stability and low anti-coloring ability in the early stage, and zinc-based thermal stabilizers are prone to "zinc burning", resulting in a decrease in thermal stability performance.

Method used

Compound rare earth stabilizers are used as the main component, combined with organozinc metal compounds, polyols and modified hydrotalcite, and the thermal stability and dispersion of the composite heat stabilizers are improved through ball milling and surface modification.

Benefits of technology

The composite thermal stabilizer is achieved environmentally friendly, strong thermal stability, and has both initial and long-term stability effects, improving the thermal stability performance of PVC materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of heat stabilizers, and provides a composite heat stabilizer and a preparation method thereof.The composite heat stabilizer is prepared from, by weight, 5-15 parts of a composite rare earth stabilizer, 2-8 parts of an organic zinc metal compound, 2-8 parts of polyol, 0.5-3 parts of modified hydrotalcite, 1-5 parts of filler and 0.5-2 parts of a lubricant. The composite heat stabilizer provided by the invention has the characteristics of environmental protection, high heat stability and initial and long-term stable effects, and has better commercial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heat stabilizers, and in particular to a composite heat stabilizer and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is a low-cost, high-performance plastic. It is one of the three major general-purpose plastics and is widely used. However, during the production and use of PVC, HCl removal reaction will occur, which can easily cause PVC degradation. Heat stabilizer is an important additive that can prevent or reduce cross-linking or degradation of PVC resin due to heat during processing and extend the service life of PVC products.

[0003] As people's environmental awareness increases, low-cost but highly toxic and polluting lead salts and heavy metal soap heat stabilizers have gradually lost their market advantages. Therefore, the development of non-toxic, environmentally friendly and efficient heat stabilizers has become an urgent need for the sustainable development of the plastics industry. Among them, rare earth heat stabilizers refer to additives made from rare earth elements as the main raw materials. Because rare earth elements have a high atomic number and a more complex electronic structure, they can absorb and convert energy through various mechanisms such as absorption, scattering and emission, thereby effectively improving the heat resistance and stability of the material. In addition, rare earth heat stabilizers have the advantages of being non-toxic and environmentally friendly, and have great development potential.

[0004] Although rare earth heat stabilizers have the above-mentioned excellent characteristics, the biggest problem with single rare earth heat stabilizers is poor thermal stability and low anti-coloring ability in the initial stage of action. Therefore, they need to be combined with polyols and other heat stabilizers such as zinc-based heat stabilizers to form a composite heat stabilizer. However, zinc-based heat stabilizers still have the problem of "zinc burning", which may lead to a decrease in the thermal stability of the composite heat stabilizer.

[0005] Patent CN 107163443B discloses an acetylacetone rare earth composite heat stabilizer and its PVC material. The raw materials of the composite heat stabilizer include acetylacetone rare earth, organic zinc metal compound, auxiliary heat stabilizer, lubricant and filler, which can effectively improve the initial colorability and long-term thermal stability of PVC. However, although the auxiliary heat stabilizer in the application is hydrotalcite, which can effectively solve the problem of "zinc burning" of zinc-based heat stabilizer, it does not solve the problem of poor dispersibility of hydrotalcite, which may lead to a decrease in the thermal stability of the composite heat stabilizer.

[0006] Therefore, there is an urgent need in the market for a composite heat stabilizer that is environmentally friendly, has strong thermal stability, and has both initial and long-term stabilization effects. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention uses a composite rare earth stabilizer as the main component of the heat stabilizer, and combines it with organic zinc metal compounds, polyols and modified hydrotalcite to synthesize a composite heat stabilizer, which has the characteristics of environmental protection, strong thermal stability and both initial and long-term stabilization effects.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] On one hand, the present invention provides a composite heat stabilizer, which comprises the following raw materials in parts by weight: 5-15 parts of a composite rare earth stabilizer, 2-8 parts of an organic zinc metal compound, 2-8 parts of a polyol, 0.5-3 parts of a modified hydrotalcite, 1-5 parts of a filler, and 0.5-2 parts of a lubricant.

[0010] The organic zinc metal compound is zinc stearate or zinc acetylsalicylate; the filler is at least one of calcium carbonate, silicon dioxide and titanium dioxide; and the lubricant is epoxidized soybean oil or polyethylene wax.

[0011] In some embodiments of the present invention, the method for preparing the composite rare earth stabilizer comprises the following steps:

[0012] (1) adding cerium nitrate and lanthanum nitrate to deionized water, stirring to obtain solution 1 for use, adding 4-propylpiperidine-4-carboxylic acid to deionized water, heating to 60-70° C., stirring, adding solution 1, stirring, adding ammonia water to adjust the pH to 6-7, stirring, boiling and evaporating until solid appears, drying, washing, and drying to obtain rare earth stabilizer 1 for use;

[0013] (2) adding cerium nitrate and lanthanum nitrate to anhydrous ethanol, stirring to obtain solution 2 for later use, adding 7-ketooctanoic acid to anhydrous ethanol, heating to 70-80° C., stirring, adding solution 2, stirring, adding anhydrous ethanol solution of sodium hydroxide, stirring, cooling to room temperature, rotary evaporation, washing, and drying to obtain rare earth stabilizer 2 for later use;

[0014] (3) The rare earth stabilizer 1 of step (1) and the rare earth stabilizer 2 of step (2) are mixed, stirred, and ball-milled to obtain a composite rare earth stabilizer.

[0015] In some embodiments of the present invention, in step (1), the molar ratio of cerium nitrate, lanthanum nitrate and 4-propylpiperidine-4-carboxylic acid is 1:(2.5-3.5):(2.5-3.5).

[0016] Preferably, in step (1), the molar ratio of cerium nitrate, lanthanum nitrate and 4-propylpiperidine-4-carboxylic acid is 1:3:3.

[0017] In some embodiments of the present invention, in step (2), the molar ratio of cerium nitrate, lanthanum nitrate and 7-ketooctanoic acid is 1:(2.5-3.5):(4.5-5.5).

[0018] Preferably, in step (2), the molar ratio of cerium nitrate, lanthanum nitrate and 7-ketooctanoic acid is 1:3:5.

[0019] In some embodiments of the present invention, in step (3), the mass ratio of rare earth stabilizer 1 to rare earth stabilizer 2 is 1:(1-2).

[0020] Preferably, in step (3), the mass ratio of rare earth stabilizer 1 to rare earth stabilizer 2 is 1:1.5.

[0021] Rare earth stabilizer is a stabilizer synthesized with carboxylates or fatty acid salts containing rare earth elements as the main ingredients. It is not only safe and environmentally friendly, but also has excellent thermal stability, light stability, transparency and tinting strength. However, rare earth stabilizers generally have the problems of poor initial thermal stability and poor inhibition of tinting properties.

[0022] The applicant selected cerium nitrate, lanthanum nitrate and 4-propylpiperidine-4-carboxylic acid as raw materials and cerium nitrate, lanthanum nitrate and 7-ketooctanoic acid as raw materials to prepare rare earth stabilizer 1 and rare earth stabilizer 2 respectively, and mixed rare earth stabilizer 1 and rare earth stabilizer 2 by ball milling to obtain a composite rare earth stabilizer. On the one hand, rare earth lanthanum has a strong ability to absorb HCl gas and can significantly improve thermal stability, but it is expensive. The applicant uses a specific ratio of cerium nitrate and lanthanum nitrate as a composite rare earth salt, which can ensure good thermal stability while also having a good cost performance; on the other hand, the applicant The prepared rare earth stabilizer 1 has a piperidine structure, and the prepared rare earth stabilizer 2 has a keto group and a long-chain alkyl structure, so that the composite rare earth stabilizer has good thermal stability, and the composite rare earth stabilizer also has good initial thermal stability, which may be the effect brought by the keto group structure in the structure; in addition, the ball milling method used in the preparation of the composite rare earth stabilizer may cause a certain hydrogen bond effect to be produced between the piperidine group in the rare earth stabilizer 1 and the keto group in the rare earth stabilizer 2, thereby enhancing the stability of the composite rare earth stabilizer and further enhancing the thermal stability of the composite rare earth stabilizer.

[0023] In some embodiments of the present invention, the polyol is any one of pentaerythritol, 1,4-butanediol, and glycerol.

[0024] In some embodiments of the present invention, the method for preparing the modified hydrotalcite comprises the following steps:

[0025] 1) adding fluorinated graphene to an ethylene glycol aqueous solution, ultrasonicating, obtaining liquid 1 for later use, adding Zn(NO3)2·6H2O and Al(NO3)3·9H2O to deionized water, stirring, obtaining liquid 2 for later use;

[0026] 2) mixing the liquid 1 and the liquid 2 in step 1), adding a sodium hydroxide aqueous solution dropwise to adjust the pH to 6.5-7.5, reacting under reflux in an inert atmosphere, standing, centrifuging, washing, and freeze-drying to obtain a product for later use;

[0027] 3) Add the product of step 2) into deionized water, stir, add sodium stearate, heat to 75-85° C., stir for 3.5-4.5 hours, filter, wash, and dry to obtain modified hydrotalcite.

[0028] Wherein, the fluorine content of the fluorinated graphene is 40-60%.

[0029] In some embodiments of the present invention, in step 1), the mass ratio of Zn(NO3)2·6H2O, Al(NO3)3·9H2O and fluorinated graphene is 1:(1-1.2):(0.04-0.06).

[0030] Preferably, in step 1), the mass ratio of Zn(NO3)2·6H2O, Al(NO3)3·9H2O and fluorinated graphene is 1:1.1:0.05.

[0031] In some embodiments of the present invention, in step 3), the mass ratio of the product to sodium stearate is 1:(4.5-5.5).

[0032] Preferably, in step 3), the mass ratio of the product to sodium stearate is 1:5.

[0033] Hydrotalcite has good heat resistance and can effectively solve the "zinc burning problem" of zinc-based heat stabilizers. It is widely used in heat stabilizers. However, the surface of hydrotalcite has active hydroxyl functional groups, which easily form hydrogen bonds between its particles to produce agglomeration, resulting in poor surface structural stability and poor dispersibility. Moreover, most heat stabilizers are added to PVC matrix for use. The hydrophilicity of hydrotalcite makes it less compatible with hydrophobic PVC, resulting in poor dispersibility of the heat stabilizer in PVC and reduced heat stabilization.

[0034] The applicant synthesized fluorinated graphene-modified zinc-aluminum hydrotalcite (product) using Zn(NO3)2·6H2O and Al(NO3)3·9H2O as raw materials and fluorinated graphene with a fluorine content of 40-60% as a modified raw material. On the one hand, the applicant controlled the ratio of zinc to aluminum to make the zinc-aluminum hydrotalcite have good dispersibility and stability. On the other hand, fluorinated graphene introduces fluorine atoms on the basis of graphene, which has the high strength and high temperature resistance characteristics of graphene while improving the hydrophobicity of hydrotalcite, thereby making the hydrotalcite in the thermal stabilizer more compatible with the PVC matrix, thereby improving the dispersibility of the hydrotalcite; further, the applicant used sodium stearate to modify the surface of the product, thereby improving the dispersibility and thermal stability of the hydrotalcite, thereby improving the thermal stability of the composite thermal stabilizer.

[0035] Another aspect of the present invention further provides a method for preparing the composite thermal stabilizer described in the above technical solution, comprising the following steps:

[0036] The composite rare earth stabilizer, the organic zinc metal compound, the polyol, the modified hydrotalcite, the filler and the lubricant are mixed, and stirred at 1300-1700 r / min for 30-50 minutes to obtain the composite heat stabilizer.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention uses a composite rare earth stabilizer as the main component of the thermal stabilizer, and synthesizes a composite thermal stabilizer with organic zinc metal compounds, polyols and modified hydrotalcite. Through the synergistic effect of the components, the composite thermal stabilizer has the characteristics of environmental protection, strong thermal stability, and both initial and long-term stabilization effects.

[0039] (2) The present invention uses cerium nitrate, lanthanum nitrate and 4-propylpiperidine-4-carboxylic acid as raw materials and cerium nitrate, lanthanum nitrate and 7-ketooctanoic acid as raw materials to prepare rare earth stabilizer 1 and rare earth stabilizer 2, respectively, and mixes rare earth stabilizer 1 and rare earth stabilizer 2 by ball milling to obtain a composite rare earth stabilizer, thereby improving the early thermal stabilizer of the rare earth stabilizer and further improving the thermal stability of the composite rare earth stabilizer.

[0040] (3) The present invention uses Zn(NO3)2·6H2O and Al(NO3)3·9H2O as raw materials and uses fluorinated graphene with a fluorine content of 40-60% as a modified raw material to synthesize zinc-aluminum hydrotalcite modified with fluorinated graphene, and further introduces sodium stearate to synthesize the modified hydrotalcite, so that the modified hydrotalcite has good dispersibility and thermal stability.

[0041] (4) The composite heat stabilizer prepared by the present invention is environmentally friendly, has strong thermal stability, and has both initial and long-term stabilization effects. It can be widely used in the field of PVC heat stabilizers and has good commercial application value. DETAILED DESCRIPTION

[0042] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0043] In the following embodiments and comparative examples, except for the composite rare earth stabilizer and modified hydrotalcite, the other compound monomers and related reagents used can be purchased from the market. Among them, the fluorine content of fluorinated graphene is 50%, which is purchased from Beijing Beike New Materials Technology Co., Ltd.; polyethylene wax is purchased from Shanghai Dingfen Chemical Technology Co., Ltd.; PVC is purchased from Dongguan Jingke Polymer Co., Ltd.

[0044] Preparation Example 1

[0045] The synthesis method of composite rare earth stabilizer A comprises the following steps:

[0046] (1) 0.01 mol of cerium nitrate and 0.03 mol of lanthanum nitrate were added to 100 ml of deionized water, stirred for 30 min, and solution 1 was obtained for standby use; 0.03 mol of 4-propylpiperidine-4-carboxylic acid was added to 50 ml of deionized water, heated to 65° C., stirred for 30 min, solution 1 was added, stirred for 30 min, 30 wt % ammonia water was added to adjust pH=6.5, stirred for 1 h, boiled and evaporated until solid appeared, dried at 60° C. for 12 h, washed with deionized water 3 times, and dried at 60° C. for 12 h, to obtain rare earth stabilizer 1 for standby use;

[0047] (2) 0.01 mol of cerium nitrate and 0.03 mol of lanthanum nitrate were added to 100 ml of anhydrous ethanol, stirred for 30 min, and solution 2 was obtained for standby use; 0.05 mol of 7-ketooctanoic acid was added to 80 ml of anhydrous ethanol, heated to 75° C., stirred for 1 h, solution 2 was added, stirred for 30 min, 75 ml of anhydrous ethanol solution of 8 g / L sodium hydroxide was added, stirred for 1 h, cooled to room temperature, rotary evaporated, washed with deionized water 3 times, and dried at 60° C. for 12 h to obtain rare earth stabilizer 2 for standby use;

[0048] (3) 4 g of the rare earth stabilizer 1 prepared in step (1) and 6 g of the rare earth stabilizer 2 prepared in step (2) were mixed, stirred for 5 min, and ball-milled for 30 min to obtain a composite rare earth stabilizer A.

[0049] Preparation Example 2

[0050] The specific implementation manner of the composite rare earth stabilizer B is the same as that of the composite rare earth stabilizer A, except that in step (1), the molar number of 4-propylpiperidine-4-carboxylic acid is replaced with 0.02 mol.

[0051] Preparation Example 3

[0052] The specific implementation manner of composite rare earth stabilizer C is the same as that of composite rare earth stabilizer A, except that in step (2), the molar number of 7-ketooctanoic acid is replaced with 0.04 mol.

[0053] Preparation Example 4

[0054] The specific implementation method of composite rare earth stabilizer D is the same as that of composite rare earth stabilizer A, except that in step (3), the mass of rare earth stabilizer 2 is 3.5 g.

[0055] Preparation Example 5

[0056] The specific implementation method of composite rare earth stabilizer E is the same as that of composite rare earth stabilizer A, except that in step (3), the mass of rare earth stabilizer 2 is 8.5 g.

[0057] Preparation Example 6

[0058] The synthesis method of modified hydrotalcite A comprises the following steps:

[0059] 1) Add 0.5 g of fluorinated graphene to 100 ml of 50 wt% ethylene glycol aqueous solution, ultrasonicate for 1 h, and obtain liquid 1 for standby use; add 10 g of Zn(NO3)2·6H2O and 11 g of Al(NO3)3·9H2O to 100 ml of deionized water, stir for 1 h, and obtain liquid 2 for standby use;

[0060] 2) Mixing the liquid 1 and the liquid 2 in step 1), adding 30 wt % sodium hydroxide aqueous solution to adjust the pH to 7, reflux reaction for 12 h under nitrogen atmosphere, standing for 12 h, centrifuging, washing with deionized water 3 times, freeze-drying at -40°C for 12 h, and obtaining the product for use;

[0061] 3) 10 g of the product of step 2) was added to 100 ml of deionized water, stirred for 1 h, 50 g of sodium stearate was added, heated to 80° C., stirred for 4 h, filtered, washed with deionized water 3 times, and dried at 60° C. for 12 h to obtain modified hydrotalcite A.

[0062] Preparation Example 7

[0063] The specific implementation manner of modified hydrotalcite B is the same as that of modified hydrotalcite A, except that in step 1), the mass of Al(NO3)3·9H2O is replaced by 9 g.

[0064] Preparation Example 8

[0065] The specific implementation manner of modified hydrotalcite C is the same as that of modified hydrotalcite A, except that in step 1), the mass of fluorinated graphene is replaced with 0.2 g.

[0066] Preparation Example 9

[0067] The specific implementation manner of modified hydrotalcite D is the same as that of modified hydrotalcite A, except that in step 3), the mass of sodium stearate is replaced with 43 g.

[0068] Example 1

[0069] A composite heat stabilizer comprises the following raw materials, measured by weight: 10 parts of a composite rare earth stabilizer A, 5 parts of zinc stearate, 5 parts of pentaerythritol, 2 parts of modified hydrotalcite A, 3 parts of fillers and 1 part of epoxidized soybean oil.

[0070] The filler is a mixture of calcium carbonate, silicon dioxide and titanium dioxide in a mass ratio of 2:1:1.

[0071] The preparation method of the composite thermal stabilizer in this embodiment comprises the following steps:

[0072] The composite rare earth stabilizer A, zinc stearate, pentaerythritol, modified hydrotalcite A, filler and epoxidized soybean oil were mixed and stirred at 1500 r / min for 40 minutes to obtain a composite heat stabilizer.

[0073] Example 2

[0074] A composite heat stabilizer comprises the following raw materials, measured by weight: 10 parts of composite rare earth stabilizer A, 2 parts of zinc acetylsalicylate, 2 parts of glycerol, 0.5 parts of modified hydrotalcite A, 1 part of filler and 0.5 parts of polyethylene wax.

[0075] The filler is the same as in Example 1.

[0076] The preparation method of the composite thermal stabilizer in this embodiment comprises the following steps:

[0077] The composite rare earth stabilizer A, zinc acetylsalicylate, glycerol, modified hydrotalcite A, calcium carbonate and polyethylene wax were mixed and stirred at 1300 r / min for 50 min to obtain a composite heat stabilizer.

[0078] Example 3

[0079] A composite heat stabilizer comprises the following raw materials by weight: 10 parts of composite rare earth stabilizer A, 8 parts of zinc stearate, 8 parts of 1,4-butanediol, 3 parts of modified hydrotalcite A, 5 parts of filler and 2 parts of epoxidized soybean oil.

[0080] The filler is the same as in Example 1.

[0081] The preparation method of the composite thermal stabilizer in this embodiment comprises the following steps:

[0082] The composite rare earth stabilizer A, zinc stearate, 1,4-butanediol, modified hydrotalcite A, filler and epoxidized soybean oil were mixed and stirred at 1700 r / min for 30 minutes to obtain a composite heat stabilizer.

[0083] Example 4

[0084] A composite heat stabilizer comprises the following raw materials by weight: 5 parts of composite rare earth stabilizer A, 3 parts of zinc stearate, 3 parts of pentaerythritol, 2 parts of modified hydrotalcite A, 2 parts of filler and 0.6 parts of epoxidized soybean oil.

[0085] The filler is a mixture of calcium carbonate and silicon dioxide with a mass ratio of 1:1.

[0086] The preparation method of the composite heat stabilizer in this example is the same as that in Example 1.

[0087] Example 5

[0088] A composite heat stabilizer comprises the following raw materials, measured by weight: 15 parts of composite rare earth stabilizer A, 7 parts of zinc stearate, 7 parts of pentaerythritol, 2 parts of modified hydrotalcite A, 4 parts of titanium dioxide and 1.5 parts of polyethylene wax.

[0089] The preparation method of the composite heat stabilizer in this example is the same as that in Example 1.

[0090] Example 6

[0091] This embodiment provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite rare earth stabilizer B replaces the composite rare earth stabilizer A in equal amounts.

[0092] Example 7

[0093] This embodiment provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite rare earth stabilizer C replaces the composite rare earth stabilizer A in equal amounts.

[0094] Example 8

[0095] This embodiment provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite rare earth stabilizer A is replaced by the composite rare earth stabilizer D in equal amounts.

[0096] Example 9

[0097] This embodiment provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the composite rare earth stabilizer E replaces the composite rare earth stabilizer A in equal amounts.

[0098] Example 10

[0099] This embodiment provides a composite heat stabilizer and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that the modified hydrotalcite B replaces the modified hydrotalcite A in equal amounts.

[0100] Embodiment 11

[0101] This embodiment provides a composite heat stabilizer and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that the modified hydrotalcite C replaces the modified hydrotalcite A in equal amounts.

[0102] Example 12

[0103] This embodiment provides a composite heat stabilizer and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that the modified hydrotalcite D replaces the modified hydrotalcite A in equal amounts.

[0104] Comparative Example 1

[0105] This comparative example provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that rare earth stabilizer 1 is used to replace composite rare earth stabilizer A in an equal amount.

[0106] The preparation method of rare earth stabilizer 1 is the same as that of Preparation Example 1.

[0107] Comparative Example 2

[0108] This comparative example provides a composite thermal stabilizer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that rare earth stabilizer 2 is used to replace composite rare earth stabilizer A in an equal amount.

[0109] The preparation method of rare earth stabilizer 2 is the same as that of Preparation Example 2.

[0110] Comparative Example 3

[0111] This comparative example provides a composite heat stabilizer and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of commercially available conventional hydrotalcite is used to replace the modified hydrotalcite A.

[0112] Commercially available conventional hydrotalcite was purchased from Jiangsu Jufeng Chemical Technology Co., Ltd.

[0113] Performance Testing

[0114] The initial and long-term thermal stability properties of the composite thermal stabilizers of Examples 1-12 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0115] 100 g of PVC was mixed with 1 g of the composite heat stabilizer of Examples 1-12 and Comparative Examples 1-3 in a high-speed mixer for 30 min, and then placed on a double-roll mill and mixed at 200° C. for 30 min to obtain PVC samples. The PVC samples were tested, and samples without the addition of the composite heat stabilizer were used as controls.

[0116] (1) Initial thermal stability

[0117] The initial thermal stability of the composite thermal stabilizer is determined by testing the initial color change time of the PVC sample using the Congo red method. The later the initial color change time, the better the initial thermal stability. Refer to standard GB / T 2917.1-2002.

[0118] (2) Long-term thermal stability

[0119] The PVC sample was cut into a 15mm×15mm square and subjected to a heat oven aging test at 180°C by the heat oven method. The long-term thermal stability of the composite thermal stabilizer was judged by observing the color change of the sample after 120 minutes. The lighter the color, the better the long-term thermal stability. The reference standard is GB / T 9349-2002.

[0120] Table 1

[0121] Group Color change time (min) Color at 120min Example 1 145 White Example 2 143 White Example 3 142 White Example 4 144 White Example 5 141 White Example 6 129 Light yellow Example 7 127 Light yellow Example 8 128 Light yellow Example 9 126 Light yellow Example 10 132 Light yellow Embodiment 11 130 Light yellow Example 12 131 Light yellow Comparative Example 1 123 brown Comparative Example 2 121 brown Comparative Example 3 125 brown Comparison 110 Brown and black

[0122] It can be seen from the data in Table 1 that the composite thermal stabilizer in Examples 1-5 of the present invention starts to change color later as a whole and the color is lighter at 120 minutes, that is, it has good initial and long-term thermal stability. Among them, Examples 6-9 change the proportion of key components in the synthesis process of the composite rare earth stabilizer, so that the initial thermal stability of the composite rare earth stabilizer is not well improved, and the long-term thermal stability is also affected to a certain extent; Examples 10-12 change the addition ratio of Al(NO3)3·9H2O, fluorinated graphene and sodium stearate during the preparation of modified hydrotalcite, so that the dispersibility of the modified hydrotalcite is not well improved, which leads to a decrease in the initial and long-term thermal stability of the composite thermal stability; Comparative Examples 1-3 are respectively selected to replace the composite rare earth stabilizer A with the same amount of rare earth stabilizer 1 and rare earth stabilizer 2, and the modified hydrotalcite A with the same amount of commercially available conventional hydrotalcite, and the test finds that the initial and long-term thermal stability of the composite thermal stabilizer show poor results.

[0123] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite heat stabilizer, characterized in that: The composite heat stabilizer comprises the following raw materials by weight: 5-15 parts of composite rare earth stabilizer, 2-8 parts of organic zinc metal compound, 2-8 parts of polyol, 0.5-3 parts of modified hydrotalcite, 1-5 parts of filler, and 0.5-2 parts of lubricant.

2. The composite heat stabilizer according to claim 1, characterized in that The preparation method of the composite rare earth stabilizer comprises the following steps: (1) adding cerium nitrate and lanthanum nitrate to deionized water, stirring to obtain solution 1 for use, adding 4-propylpiperidine-4-carboxylic acid to deionized water, heating to 60-70° C., stirring, adding solution 1, stirring, adding ammonia water to adjust the pH to 6-7, stirring, boiling and evaporating until solid appears, drying, washing, and drying to obtain rare earth stabilizer 1 for use; (2) adding cerium nitrate and lanthanum nitrate to anhydrous ethanol, stirring to obtain solution 2 for later use, adding 7-ketooctanoic acid to anhydrous ethanol, heating to 70-80° C., stirring, adding solution 2, stirring, adding anhydrous ethanol solution of sodium hydroxide, stirring, cooling to room temperature, rotary evaporation, washing, and drying to obtain rare earth stabilizer 2 for later use; (3) The rare earth stabilizer 1 of step (1) and the rare earth stabilizer 2 of step (2) are mixed, stirred, and ball-milled to obtain a composite rare earth stabilizer.

3. The composite heat stabilizer according to claim 2, characterized in that In the step (1), the molar ratio of cerium nitrate, lanthanum nitrate and 4-propylpiperidine-4-carboxylic acid is 1:(2.5-3.5):(2.5-3.5).

4. The composite heat stabilizer according to claim 2, characterized in that In the step (2), the molar ratio of cerium nitrate, lanthanum nitrate and 7-ketooctanoic acid is 1:(2.5-3.5):(4.5-5.5).

5. The composite heat stabilizer according to claim 2, characterized in that: In the step (3), the mass ratio of rare earth stabilizer 1 to rare earth stabilizer 2 is 1:(1-2).

6. The composite thermal stabilizer according to claim 1, characterized in that The polyol is any one of pentaerythritol, 1,4-butanediol and glycerol.

7. The composite heat stabilizer according to claim 1, characterized in that The preparation method of the modified hydrotalcite comprises the following steps: 1) adding fluorinated graphene to an ethylene glycol aqueous solution, ultrasonicating, obtaining liquid 1 for later use, adding Zn(NO3)2·6H2O and Al(NO3)3·9H2O to deionized water, stirring, obtaining liquid 2 for later use; 2) mixing the liquid 1 and the liquid 2 in step 1), adding a sodium hydroxide aqueous solution dropwise to adjust the pH to 6.5-7.5, reacting under reflux in an inert atmosphere, standing, centrifuging, washing, and freeze-drying to obtain a product for later use; 3) Add the product of step 2) into deionized water, stir, add sodium stearate, heat to 75-85° C., stir for 3.5-4.5 hours, filter, wash, and dry to obtain modified hydrotalcite.

8. The composite heat stabilizer according to claim 7, characterized in that In the step 1), the mass ratio of Zn(NO3)2·6H2O, Al(NO3)3·9H2O and fluorinated graphene is 1:(1-1.2):(0.04-0.06).

9. The method for preparing a composite heat stabilizer according to claim 7, characterized in that: In the step 3), the mass ratio of the product to sodium stearate is 1:(4.5-5.5).

10. A method for preparing the composite heat stabilizer according to any one of claims 1 to 9, characterized in that: The following steps are involved: The composite rare earth stabilizer, organic zinc metal compound, polyol, modified hydrotalcite, filler and lubricant are mixed, and stirred at 1300-1700 r / min for 30-50 minutes to obtain a composite heat stabilizer.

Citation Information

Patent Citations

  • Acetylacetone-based rare earth composite heat stabilizers and their PVC materials

    CN107163443B

  • Modified nylon 66 resin, preparation method and application thereof

    CN103910876A

  • Environment-friendly PVC composite heat stabilizer

    CN106046607A

  • Modified hydrotalcite / graphene anticorrosive paint

    CN116640494A

  • Preparation method and application of composite heat stabilizer

    CN118165365A